1997
DOI: 10.1152/ajplung.1997.273.2.l478
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptors inhibit ATP-sensitive K+ channels in swine tracheal smooth muscle

Abstract: The patch-clamp technique was used to characterize a cromakalim-induced current and its regulation by muscarinic receptors in tracheal smooth muscle cells. Cromakalim (10 microM) activated a steady-state increase of 33-292 pA (91.2 +/- 8.8 pA, n = 43) in whole cell current, consistent with the activation of ATP-sensitive K+ (KATP) channels. Acetylcholine (10 nM-1 microM), added cumulatively, inhibited the cromakalim-induced current by 23.6 +/- 14.9 to 73.9 +/- 4.6%. This inhibition was blocked by pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…In swine tracheal myocytes, Nuttle & Farley (1997) have described a (±)‐cromakalim‐induced K + current which was inhibited by intracellular ATP (i.e. K ATP current).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In swine tracheal myocytes, Nuttle & Farley (1997) have described a (±)‐cromakalim‐induced K + current which was inhibited by intracellular ATP (i.e. K ATP current).…”
Section: Discussionmentioning
confidence: 99%
“…In airway smooth muscle, since glibenclamide selectively inhibits not only the membrane hyperpolarization ( Murray et al ., 1989 ), but also the K + ( 86 Rb + ) efflux ( Allen et al ., 1986 ) and the muscle relaxation induced by K + channel openers (guinea‐pig, Arch et al ., 1988 ; human, Black et al ., 1990 ), it is generally believed that glibenclamide‐sensitive K + channels are the target channels for K + channel openers. Recently, Nuttle & Farley (1997) have reported that in swine cultured tracheal smooth muscle cells, (±)‐cromakalim‐induced glibenclamide‐sensitive membrane currents are inhibited by protein kinase C through muscarinic receptors. However, there has been no direct report concerning the electrophysiological and pharmacological properties of the glibenclamide‐sensitive K + channels in tracheal myocytes by use of single‐channel recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Path clamp studies using porcine tracheal smooth muscle cells have established that ACh and PMA inhibit the activation of ATP‐sensitive K + channels (K ATP ) in response to levcromakalim ( Nuttle & Farley, 1997 ) implying that a cPKC or nPKC is responsible. Staurosporine antagonized the effect of both ACh and PMA from which the authors suggest that activation of the muscarinic receptor on porcine trachealis inhibits K ATP by a PKC‐dependent mechanism.…”
Section: Pkc and Relaxationmentioning
confidence: 99%
“…There have been few studies addressing the physiological role of K ATP channels in airway smooth muscle, though muscarinic stimulation inhibited K ATP current via PKC in swine tracheal muscle cells, consistent with a role in membrane potential and airway contractility [191]. However, a variety of synthetic K ATP channel openers are effective in relaxing airway smooth muscle in vivo as well as in vitro, indicating the presence of significant populations of K ATP channels [76].…”
Section: Airwaysmentioning
confidence: 94%